Bottle Refill Water Payment Using E-Card - Fajar Rafli; Jamaaluddin Jamaaluddin; Ahmad Ahfas (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2023)
The high demand for drinking water makes drinking water sold in many stores, it makes buyers have to enter the store first and queue to pay for it. Even though there are people who cannot wait too long. This makes people want fast and easy payment for drinking water. So a fast and easy payment tool is needed. This paper describes the payment of refillable water bottles using ESP32-based E-Card. Testing is done in three stages: (1) E-Card reading distance testing, (2) payment testing in successful conditions, and (3) payment testing in failed conditions. The first test found that the E-Card reading distance is 3.5 cm but when given an aluminum plate barrier, the E-Card cannot work. From the results of the second test the payment was as expected. And the third test states that the tool works well even in conditions of inappropriate payment. The weakness of this tool is that it cannot pay with coins.